PENGARUH MOTIVASI TERHADAP SEMANGAT KERJA DAN KINERJA KARYAWAN PADA CITRALAND WATERPARK DI UBUNG DENPASAR - Adhika, I Nyoman Resa; Parwita, Gde Bayu Surya (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.03.TAHUN.2023, 2023)
The purpose of this study was to determine and analyze the effect of motivation on work morale at Citraland Waterpark Ubung Denpasar, to determine and analyze the effect of motivation on employee performance at Citraland Waterpark Ubung Denpasar and to determine and analyze the effect of morale on employee performance at Citraland Waterpark Ubung Denpasar. The sampling technique used in this research is the saturated sampling method or the census method. Data was collected through documentation, interviews and questionnaires. The data analysis technique used in this research is path analysis which is processed using SPSS version 23 software. Morale has a positive and significant effect on employee performance at Citraland Waterpark Ubung Denpasar. Motivation has a positive and significant effect on employee performance at Citraland Waterpark Ubung Denpasar.